2014
DOI: 10.1016/j.cub.2014.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Monocular Tool Control, Eye Dominance, and Laterality in New Caledonian Crows

Abstract: Tool use, though rare, is taxonomically widespread, but morphological adaptations for tool use are virtually unknown. We focus on the New Caledonian crow (NCC, Corvus moneduloides), which displays some of the most innovative tool-related behavior among nonhumans. One of their major food sources is larvae extracted from burrows with sticks held diagonally in the bill, oriented with individual, but not species-wide, laterality. Among possible behavioral and anatomical adaptations for tool use, NCCs possess unusu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…Lateralized eye use has been observed in a wide variety of vertebrate species, including mammals (Braccini, Lambeth, Schapiro, & Fitch, 2012;Guo, Meints, Hall, Hall, & Mills, 2009;Racca, Guo, Meints, & Mills, 2012;Smith, Proops, Grounds, Wathan, & McComb, 2016;Versace, Morgante, Pulina, & Vallortigara, 2007), birds (Martinho, Burns, Von Bayern, & Kacelnik, 2014;McKenzie, Andrew, & Jones, 1998;Rogers, 2012;Ventolini et al, 2005;Zucca & Sovrano, 2008), reptiles (Bonati & Csermely, 2011;Hews & Worthington, 2001;Robins, Chen, Beazley, & Dunlop, 2005), amphibians (Vallortigara, Rogers, Bisazza, Lippolis, & Robins, 1998), and fish (Bisazza, De Santi, & Vallortigara, 1999;Bisazza, Facchin, Pignatti, & Vallortigara, 1998;Karenina, Giljov, & Malashichev, 2013). In vertebrates, the right brain hemisphere (which processes information obtained by the left eye) is thought to control emotions and spatial perception, while the left hemisphere (right eye) is responsible for attention, perceptual processing and the control of motor responses (Rogers, Vallortigara, & Andrew, 2013;Vallortigara, Chiandetti, & Sovrano, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Lateralized eye use has been observed in a wide variety of vertebrate species, including mammals (Braccini, Lambeth, Schapiro, & Fitch, 2012;Guo, Meints, Hall, Hall, & Mills, 2009;Racca, Guo, Meints, & Mills, 2012;Smith, Proops, Grounds, Wathan, & McComb, 2016;Versace, Morgante, Pulina, & Vallortigara, 2007), birds (Martinho, Burns, Von Bayern, & Kacelnik, 2014;McKenzie, Andrew, & Jones, 1998;Rogers, 2012;Ventolini et al, 2005;Zucca & Sovrano, 2008), reptiles (Bonati & Csermely, 2011;Hews & Worthington, 2001;Robins, Chen, Beazley, & Dunlop, 2005), amphibians (Vallortigara, Rogers, Bisazza, Lippolis, & Robins, 1998), and fish (Bisazza, De Santi, & Vallortigara, 1999;Bisazza, Facchin, Pignatti, & Vallortigara, 1998;Karenina, Giljov, & Malashichev, 2013). In vertebrates, the right brain hemisphere (which processes information obtained by the left eye) is thought to control emotions and spatial perception, while the left hemisphere (right eye) is responsible for attention, perceptual processing and the control of motor responses (Rogers, Vallortigara, & Andrew, 2013;Vallortigara, Chiandetti, & Sovrano, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Bird species that use tools, such as New Caledonian crows ( Corvus moneduloides ) and American crows ( Corvus brachyrhynchos ), have particularly wide binocular fields and can see their beak tips [20,21]; hence, their anterior blind areas are small. In the case of the New Caledonian crow, seeing along the shaft of the tool appears to be the key (rather than binocular vision) for using tools to extract food from long, narrow holes in wood [21,43]. When the tool is being used inside a narrow hole, it is held at an angle so that there is an ipsilateral eye and a contralateral eye, but only the contralateral eye can see the tool tip [43].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the New Caledonian crow, seeing along the shaft of the tool appears to be the key (rather than binocular vision) for using tools to extract food from long, narrow holes in wood [21,43]. When the tool is being used inside a narrow hole, it is held at an angle so that there is an ipsilateral eye and a contralateral eye, but only the contralateral eye can see the tool tip [43]. Without a wide binocular field that can see the beak tip, the crow would not be able to see the tool tip at all.…”
Section: Discussionmentioning
confidence: 99%
“…NC crows also have the widest binocular field of view known in birds, which was suggested to facilitate efficient tool manipulation when searching for prey (Troscianko et al, 2012). Martinho et al (2014) subsequently reported that the wide binocular field enhanced monocular viewing of the tool tip when probing in holes. The wide binocular field allows, for example, the right eye to view the tool tip when it is positioned across the mid-sagittal line on the opposite side of the head.…”
Section: Dedicated Tool Manipulation Morphologymentioning
confidence: 99%